Kompleks Kerajaan Parcel C blok C7, Putrajaya - Mohd. Nasir, Nurmuhammad Syahid; Marjunit, Farisah Najwa; Rogees, Naomi; Othman, Najwa (2024)
This report summarises our observations and learnings from our case study tour at Kompleks Kerajaan Parcel C, Blok C7 located in Putrajaya. The present research focuses on the management, execution, and economic aspects of Block C7 by HBS Engineering Sdn. Bhd. This report contains the course-required information and statistics for each chapter. All of the information and data are based on observations made during the case study tour of the site and documents provided by the maintenance staﬀ. This course requires collecting, recording, and presenting Block C7's property details, maintenance management organisation, policy and planning, building design and structural design, building condition assessment, maintenance strategy, legal and ﬁnancial aspects, and problem analysis and recommendations. The report will conclude with the study's overall ﬁndings. All information, analysis, and explanation are based on the information provided by the management team. The oﬀered data is based on primary sources from the maintenance department, the internet, and our observations at Block C7. Maintenance management is essential for maintaining a building's quality, extending its life cycle, minimising inconvenience, and providing comfort, safety, and security to tenants and users.